Threshold and multiple indicators for nitrogen saturation in subtropical forests. (October 2018) - Yu, Qian; Duan, Lei; Yu, Longfei; Chen, Xiao; Si, Gaoyue; Ke, Piaopiao; Ye, Zhixiang; Mulder, Jan
Abstract: The influence of nitrogen (N) deposition on forest ecosystems largely depend on the N status. Developing threshold and practical indicators for N saturation in subtropical forests, with extremely high N deposition, would both enhance forest management and the assessments of global N balance and carbon (C) sequestration. Here, we quantified the N mass balance and assessed current N status at a number of subtropical forest sites in South China, using both N content, C/N ratio, and 15 N natural abundance (δ 15 N) as potential indicators of N saturation. Among the studied sites, N deposition ranged from 13.8 to 113 kg N ha −1 yr −1 in throughfall, and was dominated by ammonium (NH4 + ). The threshold for N leaching in subtropical forest was first found to be 26–36 kg N ha −1 yr −1, which was 160% higher than in temperate forest (based on prescribed minimum). This indicates that critical parameter inputs in global models of the impact of N deposition are in need of revision, based on specific ecosystem characteristics. We found a critical C/N ratio of 20 for the O/A horizon as indicator of N saturation. Foliar N content and δ 15 N were positively correlated with N deposition and were well suited to indicate regional N status. The δ 15 N enrichment factor ( Ɛ foli/So2, δ 15 Nfoliage - δ 15 NSoil2 ) was between −10‰ and −1‰, and had similar trend to those obtained from other regions with increasing N deposition. These suggest that the enrichment factor could be used to investigate the influence of N deposition in forest ecosystems, regardless of spatial heterogeneity in δ 15 N of N input, soil N availability and geomorphology. Graphical abstract: Highlights: Compared with temperate, a 160% higher threshold for N leaching in subtropical forests was first found to be 26–36 kg N ha −1 yr −1 . Foliar N% and δ 15 N, as well as C/N ratios of O/A horizon could be reliable indicators for regional N. The enrichment factor is found to be more powerful to the investigation of N status, regardless of spatial heterogeneity. Abstract : The threshold for N leaching in subtropical forest was first found to be 26–36 kg N ha −1 yr −1 .